Trauma-informed approaches to primary and community mental health care: protocol for a mixed-methods systematic review - Gene Feder; John Macleod; Katrina M Turner; Shoba Dawson; Angel Bierce; Stan Zammit; Natalia V Lewis (BMJ Open)
Introduction Exposure to different types of psychological trauma may lead to a range of adverse effects on trauma survivors, including poor mental and physical health, economic, social and cognitive functioning outcomes. Trauma-informed (TI) approaches to care are defined as a service system grounded in and directed by an understanding of how trauma affects the survivors’ neurological, biological, physiological and social development. TI service system involves training of all staff, service improvements and sometimes screening for trauma experiences. The UK started incorporating TI approaches into the National Health Service. While policies recommend it, the evidence base for TI approaches to healthcare is not well established. We aim to conduct a systematic review to synthesise evidence on TI approaches in primary and community mental healthcare globally.Methods and analysis We will undertake a systematic search for primary studies in Medline, Embase, PsycINFO, Cumulative Index to Nursing and Allied Health Literature, Cochrane library, websites of organisations involved in the development and implementation of TI approaches in healthcare, and databases of thesis and dissertation. Included studies will be in English published between 1990 and February 2020. Two reviewers will independently perform study selection with data extraction and quality appraisal undertaken by one reviewer and checked for accuracy by a second reviewer. A results-based convergent synthesis will be conducted where quantitative (narratively) and qualitative (thematically) evidence will be analysed separately and then integrated using another method of synthesis. We set up a trauma survivor group and a professional group to consult throughout this review.Ethics and dissemination There is no requirement for ethical approval for this systematic review as no empirical data will be collected. The findings will be disseminated through a peer-reviewed publication, scientific and practitioner conferences, and policy briefings targeted at local and national policy makers.PROSPERO registration number CRD42020164752.